TI_GERICHTE 11.2017.53 vom 13. August 2018 , Ipoteca legale degli artigiani e imprenditori: iscrizione provvisoria - TI Tribunale d'appello (2018)
Ipoteca legale degli artigiani e imprenditori: iscrizione provvisoria